On the inverse identification of Lankford coefficients using geometrical changes under quasi-biaxial loading - Graser, Matthias; Lenzen, Matthias; Merklein, Marion (International Journal of Material Forming, 2019)
Finite element simulation has become an important tool of process and production design in various fields, especially in the automotive industry. The calculation of forming processes in the early concept phase of new cars allows virtual adaptions, which can reduce costs of later phases in the product development significantly. Therefore, the precise characterization and modelling of the material behavior is necessary to ensure a robust and reliable numerical process design. The mechanical properties of numerous materials are highly influenced by the rolling or extrusion direction in the production process. This necessitates the characterization of materials in different loading directions. However, depending on the dimensional aspects of the semi-finished product, the manufacturing of specimens can be challenging or even impossible. Thus, in this investigation, an innovative, indirect approach for the identification of the Lankford coefficient in transversal direction is presented. Based on numerical and experimental data of layer compression tests the Lankford coefficient is determined by inverse modelling of the resulting specimen contour. Due to the characteristics of the layer compression test, it can even be used for semi-finished products with small transversal dimensions like extruded profiles. The presented methodology is on the one hand verified by conventional uniaxial tensile tests for aluminum as well as steel blank material. On the other hand it is used to determine Lankford coefficients for an aluminum extrusion hollow profile and the inversely identified material model is validated by comparison of strain distributions of experimental and numerical square tube bending tests.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Inverse parameter identification; Lankford coefficient; Layer compression test; Material modelling